Trocar-based surgical technique for drainage of suprachoroidal hemorrhages (Canadian Eye Care Today, 2023)
Suprachoroidal hemorrhage (SCH) most commonly occurs during or following intraocular surgery or in the setting of trauma. SCH requires early recognition and appropriate monitoring to prevent severe vision loss. Fortunately, some cases of SCH are self-limited and can resolve spontaneously with careful observation. However, in cases of large, progressive or appositional SCH, surgical drainage is often necessary to prevent further complications such as retinal detachment; angle-closure glaucoma; retinal incarceration; or expulsion of intraocular contents, all of which can be associated with permanent vision loss and a guarded prognosis.The traditional approach to SCH drainage involves external drainage via a 2.0 mm to 3.0 mm sclerotomy window or tunnel at the apex of the choroidal detachment. In some cases, a cyclodialysis spatula can be introduced into the suprachoroidal space to expedite outflow. Problematically, this technique can often result in post-operative leakage and hypotony, endophthalmitis, retinal incarceration, and the need for subsequent pars plana vitrectomy (PPV). Although transconjunctival trocar-cannula drainage techniques have been previously described in the literature, there is often ambiguity and ambivalence regarding vitreous substitutes (e.g., air vs gas, vs silicone oil tamponade) following drainage of choroidal hemorrhage. Here, we discuss and present a case demonstrating external trans-conjunctival drainage of SCH utilizing vitreoretinal trocar-cannulas on a patient with SCH following glaucoma surgery. Additionally, we discuss the efficacy and safety advantages of this surgical approach compared to those of previous drainage methods.